2008
DOI: 10.1016/j.str.2008.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Partitivirus Structure Reveals a 120-Subunit, Helix-Rich Capsid with Distinctive Surface Arches Formed by Quasisymmetric Coat-Protein Dimers

Abstract: Two distinct partitiviruses, Penicillium stoloniferum viruses S and F, can be isolated from the fungus Penicillium stoloniferum. The bisegmented dsRNA genomes of these viruses are separately packaged in icosahedral capsids containing 120 coat-protein subunits. We used transmission electron cryomicroscopy and three-dimensional image reconstruction to determine the structure of Penicillium stoloniferum virus S at 7.3 A resolution. The capsid, approximately 350 A in outer diameter, contains 12 pentons, each of wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
58
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 47 publications
7
58
0
Order By: Relevance
“…Even in capsids with a smaller triangulation number, such as the T ϭ 7 capsid observed by heterologous expression of selected IBDV proteins (11), space would be sufficient to accommodate a single genome copy. Furthermore, fungal viruses with multipartite dsRNA genomes, such as chrysovirus (25) and partitivirus (26), package each dsRNA segment in separate particles rather than in a single capsid. This feature is also described for comovirus, a group of plant viruses with a genome consisting of 2 molecules of positive-strand ssRNA (27).…”
Section: Discussionmentioning
confidence: 99%
“…Even in capsids with a smaller triangulation number, such as the T ϭ 7 capsid observed by heterologous expression of selected IBDV proteins (11), space would be sufficient to accommodate a single genome copy. Furthermore, fungal viruses with multipartite dsRNA genomes, such as chrysovirus (25) and partitivirus (26), package each dsRNA segment in separate particles rather than in a single capsid. This feature is also described for comovirus, a group of plant viruses with a genome consisting of 2 molecules of positive-strand ssRNA (27).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas there are numerous functional and structural studies of the family Reoviridae, it is clear that deeper characterization of many fungal and protozoal dsRNA viruses is needed. Recent studies of fungal viruses of the family Partitiviridae identified the first Tϭ1 capsid formed by quasisymmetric CP dimers (48,49); an equivalent structure in viruses in higher eukaryotes, the picobirnaviruses, was also recently described (18). Another notable example is infectious myonecrosis virus (IMNV), a shrimp pathogen with a totivirus-like 120-subunit capsid.…”
Section: Discussionmentioning
confidence: 99%
“…These capsids are an extended feature of dsRNA viruses (Fig. 1); they are described (i) in members of the family Reoviridae (37,44,69,71), which infect mostly higher eukaryotic systems, (ii) in viruses of the family Picobirnaviridae (18), a recently established taxonomic family whose members infect humans and other vertebrates, (iii) in bacteriophages of the family Cystoviridae, which infect the prokaryote Pseudomonas syringae (26,28), (iv) and in viruses of the families Totiviridae (12,13,67) and Partitiviridae (48), which mostly infect unicellular and simple eukaryotes (fungi and protozoa). A notable exception is the Penicillium chrysogenum virus (PcV) of the family Chrysoviridae, which has an authentic Tϭ1 capsid formed by just 60 copies of one polypeptide (11).…”
mentioning
confidence: 99%
“…Small aliquots (2 to 3 l) of purified SsPV1 virions were vitrified, and cryo-EM image data were recorded essentially as described previously for the partitivirus Penicillium stoloniferum virus S (PsV-S) (25). A total of 23 micrographs were recorded at 200 keV under low-dose conditions (ϳ15 e/Å 2 ) at underfocus settings ranging between 3.8 and 11 m on a Gatan Ultrascan 4K 2 charge-coupled-device (CCD) camera with an FEI Polara Tecnai microscope at a nominal magnification of ϫ76,900 (yielding an effective pixel size of 1.8 Å).…”
Section: Methodsmentioning
confidence: 99%
“…A system in which partitivirus particles (i.e., Rosellinia necatrix partitivirus 1-W8 [RnPV1-W8]) can be transfected into fungal protoplasts has been successfully established and was utilized to confirm that RnPV1-W8 has a broad host range in Sordariomycetes (23,24). Particle structures determined by cryo-electron microscopy (cryo-EM) and three-dimensional (3D) image reconstruction, as well as one determined by X-ray crystallography, have shown three different partitivirus capsids to have a so-called "Tϭ2" organization comprising 60 capsid protein (CP) dimers arranged on a Tϭ1 icosahedral lattice (25)(26)(27). These developments and technological advances have facilitated research on different aspects of the biology of fungal partitiviruses, such as virus-host interactions, virion structure, virus evolution, and host range.…”
mentioning
confidence: 99%